Ludność Warszawy w świetle spisów podatkowych z I połowy XVII wieku = The population of Warsaw in the light of tax censuses from the first half of the 17th century - Belzyt, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Tax lists of early modern cities are classified as mass sources that make it possible to estimate the number of inhabitants and to show their professional, financial and ethnic structure. It is important to carefully apply appropriate methods of criticizing historical sources and conversion factors that indicate the size of the family at that time or the number of people living in one house, another for the city and the suburbs. When examining the cultural and ethnic affiliation of the townspeople (based on the wording of the surname), caution is especially recommended, because it is not a completely sure method, and people who lived in the city for a long time underwent cultural assimilation.
Keywords: tax registers in modern cities; Warsaw; population structure; spisy podatkowe w miastach nowożytnych; Warszawa; struktura ludności